2021
DOI: 10.3389/fimmu.2021.690697
|View full text |Cite
|
Sign up to set email alerts
|

PARK7 Protects Against Chronic Kidney Injury and Renal Fibrosis by Inducing SOD2 to Reduce Oxidative Stress

Abstract: Renal fibrosis is the final common pathway to chronic kidney diseases regardless of etiology. Parkinson disease protein 7 (PARK7) is a multifunctional protein involved in various cellular processes, but its pathophysiological role in kidneys remain largely unknown. Here, we have determined the role of PARK7 in renal fibrosis and have further elucidated the underlying mechanisms by using the in vivo mouse model of unilateral ureteric obstruction (UUO) and the in vitro model of transforming growth factor-b (TGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…In this paper, we found a deficiency in the antioxidant capacity of UUO or CIN kidney, previous research found UUO induction resulted in impaired renal function along with the downregulation of antioxidant proteins, such as NRF2, NQO1 and SOD, as a result, more ROS produced finally leads to oxidative stress and fibrosis [38,39]. While the expression of SOD2, an antioxidant enzyme, can protect against chronic kidney injury and renal fibrosis by reducing oxidative stress in renal tubular cells [40,41]. Peroxisome proliferator-activated receptors (PPARs) are a kind of transcription factor having anti-inflammatory effects, one study found the activation of PPAR-α by PPAR agonists can improve UUO phenotype [42].…”
Section: Discussionmentioning
confidence: 58%
“…In this paper, we found a deficiency in the antioxidant capacity of UUO or CIN kidney, previous research found UUO induction resulted in impaired renal function along with the downregulation of antioxidant proteins, such as NRF2, NQO1 and SOD, as a result, more ROS produced finally leads to oxidative stress and fibrosis [38,39]. While the expression of SOD2, an antioxidant enzyme, can protect against chronic kidney injury and renal fibrosis by reducing oxidative stress in renal tubular cells [40,41]. Peroxisome proliferator-activated receptors (PPARs) are a kind of transcription factor having anti-inflammatory effects, one study found the activation of PPAR-α by PPAR agonists can improve UUO phenotype [42].…”
Section: Discussionmentioning
confidence: 58%
“…After adaptive feeding for 7 days, 36 SPF male Sprague–Dawley rats (200 ± 20 g) were randomly divided into the following groups (n = 6 per group): Sham, Model, Losartan Potassium Tablets (LP), YSHXD low-, medium-, and high-dose; The rat model of RF was established using unilateral ureteral ligation (UUO) as previously described; 53 , 54 rats in the sham group underwent the same procedure but without ligation of disconnection of the ureter. The low-, medium- and high-dose YSHXD groups were administered (through gavage) oral doses of 3.94 g·kg −1 , 7.88 g·kg −1 and 15.75 g·kg −1 YSHXD (at a 1:1 ratio), respectively, based on the conversion of body surface area between rats and humans.…”
Section: Methodsmentioning
confidence: 99%
“…Few previous studies have investigated how DJ-1 regulates the physiological function of glomerular podocytes ( 10 , 11 ). It has been suggested that autophagy activation and the inhibition of apoptosis have protective effects in high glucose-induced podocyte injury models, and that this protective effect is associated with DJ-1( 12 ).…”
Section: Introductionmentioning
confidence: 99%